Effects of flaxseed (Linum usitatissimum) on climacteric symptoms and clinical parameters in post-menopausal women: Flaxseed effects on menopause associated symptoms and biochemical parameters - Kawa Dizaye; Adeeb Alchalabi , , Dereen; Marouf, Bushra Hassan (Iraqi Journal of Pharmaceutical Sciences, 2023)
Menopause is the irreversible and permanent cessation of menstruation after one year of amenorrhea. Common symptoms include vaginal dryness, hot flashes, night sweating, and bone pain. Traditionally Linum usitatissimum (Flaxseeds) has been used for the treatment of postmenopausal symptoms. However, the effect of this medicinal herb on the satiety hormone; leptin and body weight in menopausal women has not been elucidated well. This study was designed to evaluate the effect of flaxseeds on serum estrogen, progesterone, leptin, and malondialdehyde, body mass index, blood pressure in menopausal women. Moreover, the flaxseed effect on climacteric symptoms was also investigated. The study was carried out as an interventional pre-post design. The study was a six-week oral administration of 1000 mg flaxseed powder twice daily by menopausal women. The duration of the study was eight months. Serum levels of estrogen, progesterone, and leptin hormones as well as total plasma malondialdehyde were determined pre-and-post flaxseed intervention. Clinical symptoms and bothersome complaints of postmenopausal women such as hot flashes, vaginal dryness, bone pain, and night sweating were also evaluated. Furthermore, blood pressure elements and body mass index were also measured. The results showed that Linum usitatissimum seed powder significantly reduced vaginal dryness, hot flashes, bone pain, and night sweating in menopausal women. The same dose of flaxseed had no significant effects on serum estrogen and progesterone. However, it significantly decreased serum malondialdehyde and increased serum leptin. Flaxseed had a non-significant effect on body mass index and blood pressure. In conclusion Linum usitatissimum seed had significant efficacy in relieving vasomotor symptoms, decreasing oxidative stress, and increasing serum levels of leptin in menopausal women. Keywords: climacteric, estrogen, progesterone, leptin, malondialdehyde.